2005
DOI: 10.4141/s03-055
|View full text |Cite
|
Sign up to set email alerts
|

Effets de boues mixtes de papetières fraîches et compostées sur l’agrégation du sol, l’inclusion et la minéralisation du C dans les macro-agrégats stables à l’eau

Abstract: Bipfubusa, M., N'Dayegamiye, A. et Antoun, H. 2005. Effets de boues mixtes de papetières fraîches et compostées sur l'agrégation du sol, l'inclusion et la minéralisation du C dans les macro-agrégats stables à l'eau. Can. J. Soil Sci. 85: 47-55. L'agrégation du sol peut dépendre des caractéristiques physiques et chimiques des matières organiques incorporées. L'objectif de cette étude était de définir les effets des boues mixtes de papetières fraîches (BF) et compostées (BC), et la fréquence de leurs application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…Application of FDS, CDS, or N fertilizer significantly increased soil macroaggregates (>2 mm) and the mean-weight diameter of aggregates, compared to the unamended, unfertilized control (Table 2; contrast 1). As in this study, Chantigny et al [28] and Bipfubusa et al [29] indicated that paper sludges applications rapidly increased soil macroaggregates proportions and stability. Compared to the control, the application of FDS or CDS contributed to the formation of larger macroaggregates (>5 mm and 2-5 mm) probably due to the increase of organic binding agents that form macroaggregates such as polysaccharides, microbial products, phenolic substances, and humic substances [10,30] Surprisingly, N fertilizer also increased the proportion of soil macroaggregates (>2 mm) Table 3: Residual effects of applications of fresh and composted paper sludges, and N fertilizer on soil bulk density, nitrogen and carbon contents, C/N ratio, and C (Mg ha −1 ) at 0-10-cm soil layer in 2004.…”
Section: Resultssupporting
confidence: 70%
“…Application of FDS, CDS, or N fertilizer significantly increased soil macroaggregates (>2 mm) and the mean-weight diameter of aggregates, compared to the unamended, unfertilized control (Table 2; contrast 1). As in this study, Chantigny et al [28] and Bipfubusa et al [29] indicated that paper sludges applications rapidly increased soil macroaggregates proportions and stability. Compared to the control, the application of FDS or CDS contributed to the formation of larger macroaggregates (>5 mm and 2-5 mm) probably due to the increase of organic binding agents that form macroaggregates such as polysaccharides, microbial products, phenolic substances, and humic substances [10,30] Surprisingly, N fertilizer also increased the proportion of soil macroaggregates (>2 mm) Table 3: Residual effects of applications of fresh and composted paper sludges, and N fertilizer on soil bulk density, nitrogen and carbon contents, C/N ratio, and C (Mg ha −1 ) at 0-10-cm soil layer in 2004.…”
Section: Resultssupporting
confidence: 70%
“…The three other treatments had similar N concentrations across all size classes. Upon aggregate breakdown, occluded N and C within aggregates are mineralized into forms available for plants and microorganisms (Bipfubusa et al, 2005). Considering that N content in all aggregate size classes was similar in the Bio‐20 treatment and the control, it appears that the increase in the soil organic N pool from the Bio‐20 treatment was either insufficient to generate a detectable difference or that it was depleted via mineralization in the subsequent 4 yr.…”
Section: Resultsmentioning
confidence: 99%
“…Our results show an increase in soil macroaggregate sizes (Σ > 0.25 mm) and in soil structural stability as indicated by the MWD of water‐stable aggregates following repeated applications of PMS and DCM, compared to the control and MF treatments. A number of studies have also shown an increase in macroaggregates and in the MWD of water‐stable aggregates following PMS applications (Nemati et al, 2000; Gagnon et al, 2001; Bipfubusa et al,.2005, 2008; N'Dayegamiye, 2006).…”
Section: Discussionmentioning
confidence: 99%